Nuclear Tau as an Early Molecular Marker of Alzheimer’s Disease - Francesca Bruno; Valentina Sturiale; Desiree Brancato; Laura Gil; Isabel M. Olazabal; Fernando Pinedo; Ana B. Rebolledo; Salvatore Saccone; Concetta Federico (Medical Sciences Forum, 2023)
Age-related neurodegenerative diseases have drawn the interest of the scientific community due to the gradual increase in the average age in the world’s population. Recent studies have indicated an altered cell cycle in the triggering of neurodegenerative diseases such as Alzheimer’s disease (AD). This process seems to involve nuclear tau, a protein which we have previously shown to have a central role in neuronal in vitro differentiation. In this work, we studied the role of the nuclear tau protein, specifically of the AT8 epitope, in the onset of AD to evaluate its possible use as an early molecular marker. The immunolocalization in neurons of the CA1 region of the human hippocampus from normal, senile, and AD subjects showed that the AT8 epitope decreases in senile neurons with respect to younger ones, indicating its possible role in the ectopic activation of the cell cycle in differentiated cells. Here, we show data that improve knowledge on the role of nuclear tau in neuronal differentiation and cell degeneration in AD, involving the presence/absence of AT8 in the nucleolus of neurons related to re-entry into the cell cycle. The molecular mechanisms related to the start of AD are not yet clear, so their understanding is relevant if we consider the social impact of this disease in human populations.